Insulin-induced Lipohypertrophy in Patients with Type 1 Diabetes Mellitus Treated with an Insulin Pump - Damian Ucieklak; Sandra Mrozinska; Aleksandra Wojnarska; Maciej T. Malecki; Tomasz Klupa; Bartłomiej Matejko (International Journal of Endocrinology)
Background. Lipohypertrophy (LH) of subcutaneous tissue is an insulin-induced complication occurring in patients with diabetes. We aimed to define the prevalence of LH and identify its risk factors in type 1 diabetes (T1DM) patients treated with continuous subcutaneous insulin infusion (CSII). Materials and Methods. The study included 79 consecutive CSII-treated T1DM patients. The diagnose of LH was based on ultrasonography (US) as a reference method, physical examination was also performed. Clinical characteristics were available from the medical records. Results. The median age of patients was 28 years (interquartile range [IQR], 24–30.5) with a body mass index (BMI) of 24.5 ± 3.5 kg/m2, HbA1c 7.1% (IQR, 6.7–8.1), T1DM duration 15 (9–20) years, and CSII use duration of 8 year (IQR, 5–11). LH was detected by US in 75 (94.9%) patients. This value was much higher than this obtained by visual assessment (n = 39, 49.4%) or palpation (n = 59, 74.7%). In univariate analyses, the following risk factors for occurrence of 5 and more LH lesions were identified: the ratio of insulin dose to body mass exceeding 0.7 IU/kg (OR, 3.69; 95% CI, 1.43–10.01) and the total daily insulin dose (OR, 1.05; 95% CI, 1.02–1.09). A higher dose of insulin per kg remained a significant risk factor of LH amount in multivariate analysis. Conclusion. This selected T1DM cohort treated with CSII had a very high prevalence of LH. US assessment should be considered as a reference method for LH screening in T1DM patients. The identified risk factors for the number of LH lesions were related to insulin dosing.